2007
DOI: 10.1111/j.1439-0531.2007.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Wapl Localization on the Synaptonemal Complex, a Meiosis‐specific Proteinaceous Structure that Binds Homologous Chromosomes, in the Female Mouse

Abstract: The wings apart-like (Wapl) protein is required to hold sister chromatids together in mitotic heterochromatin in Drosophila melanogaster. It is localized on the synaptonemal complex (SC), a meiosis-specific structure connecting one pair of sister chromatids to the homologous pair in mouse pachytene spermatocytes. The human Wapl is a cohesin-binding protein that facilitates cohesin's timely release from chromosome arms during prophase. The objective of the present study was to determine the subcellular localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…During S phase, WAPL-PDS5B function is antagonized by Sororin, which displaces WAPL from PDS5B, thereby promoting cohesin loading and/or stabilization (Shintomi and Hirano, 2009; Zhang et al, 2008). Recent studies in Caenorhabditis elegans , Saccharomyces cerevisiae and Arabidopsis thaliana demonstrated a role for WAPL in cohesin regulation during meiosis (Challa et al, 2016; Crawley et al, 2016; De et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During S phase, WAPL-PDS5B function is antagonized by Sororin, which displaces WAPL from PDS5B, thereby promoting cohesin loading and/or stabilization (Shintomi and Hirano, 2009; Zhang et al, 2008). Recent studies in Caenorhabditis elegans , Saccharomyces cerevisiae and Arabidopsis thaliana demonstrated a role for WAPL in cohesin regulation during meiosis (Challa et al, 2016; Crawley et al, 2016; De et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse oocytes, WAPL colocalizes with SYCP2 during pachytene (Zhang et al, 2008). PDS5B is present in spermatogonia and spermatocytes and during meiotic prophase is associated with the AE independently of the presence of synaptonemal complex proteins (Fukuda and Hoog, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another cytological example of the specific presence of a cohesion cofactor in meiosis is related to WAPL localization. WAPL was found on axial and lateral elements of chromosomes (AE/LEs) in some prophase I stages in mouse spermatocytes (Kuroda et al, 2005) and oocytes (Zhang et al, 2008c) colocalizing with SYCP3, a constitutive protein of the SC; however, no more extensive study has been carried out on the role of WAPL in meiosis. It has been established that WAPL and PDS5 act as a protein complex during cohesion establishment and maintenance (see Skibbens, 2009 for further details); but there is no data about the possible presence of PDS5 in mammalian prophase I.…”
Section: Roles Of the Cohesin-regulators In Meiosismentioning
confidence: 99%
“…Human WAPL regulates the resolution of sister chromatid cohesion and promotes cohesin complex removal by direct interaction with the RAD21 and SA/STAG cohesin subunits [Gandhi et al, 2006;Kueng et al, 2006]. Wapl was found on AE/LE in some prophase I stages in mouse spermatocytes [Kuroda et al, 2005] and oocytes [Zhang J et al, 2008b], colocalizing with SYCP3; however, no more extensive study has been carried out on the role of Wapl in meiosis. Further cytological and biochemical studies are needed to characterize the role of Pds5 and Wapl during meiosis.…”
Section: Regulation Of Loading Establishment Maintenance and Removamentioning
confidence: 99%